Margaret Sanger - Bachrach, Deborah, 1943- (California : Lucent Books, 1993)
Juvenile literature.
Includes bibliographical references and index.
Keywords: Birth control-United States-Biography -- Juvenile literature; Social reformers-United States-Biography -- Juvenile literature